PERENCANAAN DAN PENGADAAN SARANA PRASARANA DI MTs TAHFIZH DAN EKONOMI ISLAM (TEI) MULTAZAM – RUMPIN, BOGOR - Lukmanul Jamil, Zam zam; Erihadiana, Mohamad; Fauziah, Yunisa; Jahari, Jaja; Sariwati, Nova (Prodi Manajemen Pendidikan Islam, 2023)
The purpose of this study was to describe the planning and procurement of facilities and infrastructure at MTs Tahfizh and Islamic Economics (TEI) Multazam - Rumpin, Bogor. The research method used is a descriptive qualitative method that emphasizes the depiction of what it is and is in accordance with the reality of the facilities and infrastructure management process at MTs Tahfizh and Islamic Economics (TEI) Multazam - Rumpin, Bogor. The main subject in this research is the head of the facilities and infrastructure at the pesantren. The conclusion of this study is that the planning activities of facilities and infrastructure that are implemented in the Multazam Islamic Boarding School, Rumpin prioritize a pattern of caution and openness. From the results of the research, it was found that the planning of facilities and infrastructure implemented at the Multazam Islamic Boarding School, Rumpin emphasizes a pattern of caution and openness. While the procurement of madrasah facilities and infrastructure at the Multazam Islamic Boarding School, Bogor is carried out in several ways according to the type of facilities and infrastructure required, namely: (1) ordering, for special items such as tables, chairs, uniforms or others, (2) manufacturing, for permanent infrastructure such as buildings, sports fields, parks and others, and (3) direct purchases, for consumable goods such as office stationery (ATK), consumer goods (coffee , sugar, cakes, and others).